2014
DOI: 10.1021/nn502426c
|View full text |Cite
|
Sign up to set email alerts
|

Building Complex Hybrid Carbon Architectures by Covalent Interconnections: Graphene–Nanotube Hybrids and More

Abstract: Graphene is theoretically a robust two-dimensional (2D) sp(2)-hybridized carbon material with high electrical conductivity and optical transparency. However, due to the existence of grain boundaries and defects, experimentally synthesized large-area polycrystalline graphene sheets are easily broken and can exhibit high sheet resistances; thus, they are not suitable as flexible transparent conductors. As described in this issue of ACS Nano, Tour et al. circumvented this problem by proposing and synthesizing a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 77 publications
1
104
0
3
Order By: Relevance
“…Yet, presently designed graphene foams suffers from macroscopic dimensions and a severe miniaturization (by at least two orders of magnitude) may be required to truly benefi t from the wonder properties of graphene. [ 536,675,[681][682][683] Finally, it should be mentioned that caution must be exercised with respect to utilizing graphene or graphene analogues derivatives for energy storage or other electrochemical devices and applications. [ 684,685 ] Radich et al have recently demonstrated that rGO is not suitable platform for TiO 2 based photocatalysis.…”
Section: Graphene-inside Batteries and Capacitorsmentioning
confidence: 99%
“…Yet, presently designed graphene foams suffers from macroscopic dimensions and a severe miniaturization (by at least two orders of magnitude) may be required to truly benefi t from the wonder properties of graphene. [ 536,675,[681][682][683] Finally, it should be mentioned that caution must be exercised with respect to utilizing graphene or graphene analogues derivatives for energy storage or other electrochemical devices and applications. [ 684,685 ] Radich et al have recently demonstrated that rGO is not suitable platform for TiO 2 based photocatalysis.…”
Section: Graphene-inside Batteries and Capacitorsmentioning
confidence: 99%
“…Moreover, because of its strong π-π interaction toward other graphitic nanomaterials resulting from the similar sp 2 -carbon conjugated structures, graphene has been incorporated in building novel hybrid multidimensional carbon-based nanomaterials that combine respective advantages from different components [26], such as rebar graphene, which utilizes the carbon nanotube networks to reinforce the mechanical strength of graphene for transparent and conductive thin films [27], and graphene-CNT carpets that exhibit superior conductivity and ultra-large specific surface area for high-performance supercapacitors [28]. However, to our knowledge the use of functionalized graphene both as a functional and robust interface in carbon based hybrid systems has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…GO also appears to be an excellent precursor for synthesizing more complex and hybrid graphene-based materials [10] at affordable costs. The GO structure consists of a graphene layer modified with oxygen functional groups decorating the basal plane and edges [11].…”
Section: Introductionmentioning
confidence: 99%
“…An advantage of GO when compared to pristine graphene flakes lies in the presence of functional groups that make it ideal for applications involving composites in which matrix-filler bonding is preferred [14,18]. Therefore, the control in the fabrication of novel hybrid materials and 3-dimensional structures [10] require the development of an adequate and reliable synthesis model which could deep our knowledge in understanding the detailed structure of GO and its reduced forms. Over the past decades, different models for the structure of graphite oxide were proposed, mainly consisting of a homogeneous oxidized structure [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%